2018
DOI: 10.1093/omcr/omx101
|View full text |Cite
|
Sign up to set email alerts
|

Fournier Gangrene in a patient receiving chemo–radiation for rectal cancer

Abstract: We herein present a case of a 24-year-old patient with a cT4N+ rectal cancer who developed Fournier's gangrene (FG) 1 week after the completion of preoperative chemoradiotherapy. The patient was promptly referred to the surgical department where she was treated with antibiotics and repeated surgical debridement. FG is a rare and life-threatening situation that needs to be managed aggressively with no delay. The clinical image above is unique and characteristic of this clinical entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…(1) The patients met the diagnostic criteria for esophageal cancer and were diagnosed with different degrees of hypertension. (2) The expected survival time of patients was no less than 6 months. (3) The patients received radical surgery for esophageal carcinoma.…”
Section: Inclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…(1) The patients met the diagnostic criteria for esophageal cancer and were diagnosed with different degrees of hypertension. (2) The expected survival time of patients was no less than 6 months. (3) The patients received radical surgery for esophageal carcinoma.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…Esophageal cancer is a common malignant disease of esophageal epithelium [1]. Epidemiological studies have found that the prevalence of esophageal cancer in China is on the rise year by year, mostly in men aged 40-80 years old, with a higher incidence in urban areas than that in rural areas [2]. At present, the cause of esophageal cancer has not been found in the medical community, which may be related to nitrite, fungaltoxin, genetic factors, etc.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Diabetes mellitus, hypertension, immunosuppression, alcoholism, chronic renal failure, obesity, cortisone use, malignancy, pulmonary diseases, and systemic disorders are known to be the predisposing factors for FG. [8,9] Others include urethral obstruction, instrumentation, urinary extravasation and trauma, morbid obesity, and poor hygiene. [7,10,11] Treatment is costly due to long duration of hospital stay, serial debridement, and antibiotics usually third-generation cephalosporins, aminoglycosides, and metronidazole, [5] while others may use relatively more expensive antibiotics such as meropenem and vancomycin.…”
mentioning
confidence: 99%